Differential response in lipid levels of type 2 diabetics and non-diabetic controls to falciparum malaria - Acquah, Samuel; Egham, Benjamin Ackon; Bawa, Salifu; Boampong, Johnson Nyarko (Asian Journal of Medical Sciences, 2014)
Objective: To investigate the effects of falciparum malaria on lipid profile and atherogenic indices of type 2 diabetics and non-diabetic adults in the Central Region of Ghana. Methods: Plasma lipid profile comprising total cholesterol (CHOL), high-density lipoprotein cholesterol (HDL), low-density lipoprotein cholesterol (LDL) and triglycerides (TG) were determined in 100 type 2 diabetics and 100 non-diabetic controls before and during falciparum malaria using the BT3000 autoanalyzer in a prospective case control study design. Atherogenic indices were computed. Results: At baseline, diabetics recorded significantly (P < 0.05) lower level of LDL but higher levels of CHOL/LDL and TG/HDL ratios than controls. LDL correlated (P < 0.05) positively but negatively with CHOL and HDL respectively in the two study groups. During malaria, diabetics exhibited higher (P < 0.05) levels of CHOL and TG but lower level of HDL. Non-diabetic controls had malaria-induced elevated level in TG only. The positive correlation between LDL and CHOL was maintained in the two study groups. The TG levels of diabetics correlated (P < 0.05) positively with LDL and HDL during malaria. In the case of controls, a positive (P < 0.05) correlation was found between LDL and HDL during falciparum malaria. Conclusion: Falciparum malaria modified the associations among the various DOI: http://dx.doi.org/10.3126/ajms.v6i1.10798 Asian Journal of Medical Sciences Vol.6(1) 2015 71-76